2013
DOI: 10.1534/g3.113.008466
|View full text |Cite
|
Sign up to set email alerts
|

Extension of theCaenorhabditis elegansPharyngeal M1 Neuron Axon Is Regulated by Multiple Mechanisms

Abstract: The guidance of axons to their correct targets is a critical step in development. The C. elegans pharynx presents an attractive system to study neuronal pathfinding in the context of a developing organ. The worm pharynx contains relatively few cells and cell types, but each cell has a known lineage and stereotyped developmental patterns. We found that extension of the M1 pharyngeal axon, which spans the entire length of the pharynx, occurs in two distinct phases. The first proximal phase does not require genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 131 publications
0
10
0
Order By: Relevance
“…Studies in worms, flies, fish, and mice have identified roles for the PHR proteins in synapse formation (2)(3)(4)(5), axon guidance and extension (6 -11), and axon termination (3,(12)(13)(14).…”
mentioning
confidence: 99%
“…Studies in worms, flies, fish, and mice have identified roles for the PHR proteins in synapse formation (2)(3)(4)(5), axon guidance and extension (6 -11), and axon termination (3,(12)(13)(14).…”
mentioning
confidence: 99%
“…The proximal trajectory of the M2 axons projects straight from the cell body through the isthmus, and is impervious to mutations in growth cones or guidance cues; it must therefore be established in a growth-cone independent manner. 20 , 86 , 89 Consistently, microscopic monitoring of the M2 neuron shows that a growth cone appears only after the axon has elongated to span the nascent isthmus during early embryogenesis. This growth cone emerges within the developing metacorpus and therefore cannot participate in the elongation of the axon through the isthmus.…”
Section: Morphogenesis Of Individual Cellsmentioning
confidence: 72%
“…The developmental genetics of the M1 neuron has also been investigated in detail. 89 M1 is a unique neuron with a very long rather straight trajectory: its cell body is located within the posterior bulb and its axon extends a proximal trajectory through the isthmus, and a distal portion that projects from the metacorpus and all the way to the anterior end of the pharynx where it terminates into two short posteriorly directed branches ( Figure 1 (a)). M1 innervates the procorpus by forming synapses with the pm1, pm2, and pm3 muscle cells, while receiving input from interneurons in each of the three pharyngeal sectors.…”
Section: Morphogenesis Of Individual Cellsmentioning
confidence: 99%
See 2 more Smart Citations